Reducing depression in 9 -10 year old children in low SES schools: A longitudinal universal randomized controlled trial - Rooney, Rosanna; Hassan, Sharinaz; Kane, Robert; Roberts, Clare; Nesa, M. (Elsevier Ltd, 2013)
The Aussie Optimism: Positive Thinking Skills Program (AOP-PTS) is an innovative curriculum-based mental health promotion program based on cognitive and behavioural strategies. The program is aimed at preventing depressive and anxiety symptoms and disorders in middle primary school children aged 9–10 years. Students from 22 low SES primary schools (N = 910) were randomly assigned to an intervention or a control group and assessed at baseline, post-test, 6 months and 18 months. The intervention group received the program implemented by teachers and the control group received their regular Health Education curriculum. Students completed questionnaires on depression, anxiety, and attribution style. At risk students were further assessed with the computerised Diagnostic Interview for Children and Adolescents. Parents reported on their children's externalising and internalising problems at home. Children in the intervention condition reported a significant pre-post reduction in depressive symptoms, and there was a significant pre-post reduction in parent-reported emotional difficulties which was maintained at 6 month follow-up; no changes were evident in the control group. Both groups showed significant improvements in child-reported anxiety and attribution style, and significant improvements in parent-reported pro-social behaviours. For both groups, there were no significant post-baseline changes in incidence and recovery rates for depression, anxiety, or internalising symptoms. These findings suggest that AOP-PTS has the potential to treat depressive symptomatology in the immediate term but the effects were not sustained. There is also evidence of improved emotional resilience up to 6 months following the program. Further follow-up to investigate longer term effects is needed.